263 Radiomics of the primary tumour as a tool to improve 18F-FDG-PET sensitivity in detecting nodal metastases in women with apparent early endometrial cancer. (18th September 2019) - Buda, A; Crivellaro, C; Bernardi, E; Giuliani, D; Elisei, F; La Manna, M; Guerra, L; Delle Marchette, M; Grassi, T; Di Meo, ML; Adorni, M; Bellante, N; et al.
Abstract : Objectives: In this study we investigated the role of radiomic applied in women with endometrial cancer underwent 18F-FDG PET scan, to evaluate if imaging features computed on the primary tumor could improve sensitivity in detection of lymph node (LN) metastases. Methods: Between 1/2009 and 12/2018, 116 women underwent preoperative 18F-FDG PET/CT were considered. SUV, MTV, TLG, geometrical shape, histograms and texture features were computed inside tumor contours. In group 1 (87 patients), univariate association with LN metastases was computed by Mann-Whitney test and a neural network multivariate model was developed. Univariate and multivariate models were assessed with leave one out on 20 training sessions and on group 2 (29 patients). Results: Sensitivity and specificity of LN visual detection were 50% and 99% on group 1 and 33% and 95% on group 2. The lower sensitivity of visual detection in group 2 is mainly related to the higher rate of micrometastases (25% vs 13%). A unique heterogeneity feature computed on the primary tumor (GLSZM ZP) was able to predict LN metastases better than any other feature, or multivariate model (sensitivity and specificity of 75% and 81% in group 1 and of 89% and 80% in group 2). Tumors with LN metastases generally demonstrated a lower GLSZM ZP value, i.e. by the co-presence of high-uptake and low-uptake areas. Conclusions: In our study the computation of imaging features on the primary tumor increases nodal staging for detection sensitivity in 18F-FDG PET and can be considered for a better planning of the surgical treatment.